PENERAPAN PROJECT BASED LEARNING (PBL) UNTUK MENINGKATKAN DAYA INGAT SISWA PADA MATA PELAJARAN FIKIH DI MAN 1 BLITAR - Kamalah, Lisamatul (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
Islamic Religious Education (PAI) is organized by the government in every educational institution for students who excel in understanding and carrying out religious practices properly and correctly in everyday life. The problem that often occurs in educational institutions is t`he application of learning models that are not appropriate during the teaching and learning process, especially in PAI material. Therefore, a learning model that is not boring is needed so that students feel bored to learn it. One type of learning model that focuses on student activity is project-based learning. This study aims to explain about: (1) Planning the implementation of Project Based Learning on fiqh subjects at MAN 1 Blitar. (2) Implementation of Project Based Learning on fiqh subjects at MAN 1 Blitar. (3) Student learning outcomes in terms of learning completeness using the Project Based Learning model in Fiqh Subjects at MAN 1 Blitar. The approach in this research is descriptive qualitative research with data collection techniques in the form of observation, interviews, and documentation. The results of this study indicate that the application of the Project Based Learning model to fiqh subjects can improve student memory at MAN 1 Blitar. This can be proven based on the average value before the implementation of the Project Based Learning learning model in class XI Religion 1 which is 87.7 and after the fiqh teacher applies the project based learning learning model in class XI Religion 1 it becomes 89.4. Abstrak Pendidikan Agama Islam (PAI) diselenggarakan oleh pemerintah di setiap lembaga pendidikan guna mencetak peserta didik yang unggul dalam memahami serta melakukan praktek keagamaan dengan baik dan benar di dalam kehidupan sehari-hari. Permasalahan yang sering terjadi pada lembaga-lembaga pendidikan adalah penerapan model pembelajaran yang tidak sesuai saat proses belajar-mengajar khususnya pada materi PAI. Oleh karena itu, dibutuhkan model pembelajaran yang tidak menjenuhkan sehingga siswa merasa bosan untuk mempelajarinya. Salah satu jenis model pembelajaran yang berfokus kepada keaktifan siswa adalah project based learning. Penelitian ini bertujuan untuk menjelaskan tentang: (1) Perencanaan penerapan Project Based Learning pada mata pelajaran fikih Di MAN 1 Blitar. (2) Pelaksanaan penerapan Project Based Learning pada mata pelajaran fikih Di MAN 1 Blitar. (3) Hasil belajar siswa ditinjau dari ketuntasan pembelajaran menggunakan model Project Based Learning Pada Mata Pelajaran Fikih Di MAN 1 Blitar. Pendekatan dalam penelitian ini ialah jenis penelitian deskriptif kualitatif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Adapun hasil dari penelitian ini menunjukkan bahwa penerapan model pembelajaran Project Based Learning pada mata pelajaran fikih dapat peningkatkan daya ingat siswa di MAN 1 Blitar. Hal ini dapat dibuktikan berdasarkan kepada nilai rata-rata sebelum diterapkannya model pembelajaran Project Based Learning pada kelas XI Agama 1 yaitu 87,7 dan setelah guru fikih menerapkan model pembelajaran project based learning pada kelas XI Agama 1 menjadi 89,4.